Exploring and Predicting the Individual, Combined, and Synergistic Impact of Land-Use Change and Climate Change on Streamflow, Sediment, and Total Phosphorus Loads - Xie, Kun; Chen, Hua; Qiu, Yunfeng; Kim, Jong-Suk; Yoon, Sun-Kwon; Lin, Yunfa; Liu, Bingyi; Wang, Jun; Chen, Jie; Zhang, Shengwen (Frontiers in Environmental Science, 2021)
The present study predicts and assesses the individual, combined, and synergistic effect of land-use change and climate change on streamflow, sediment, and Total Phosphorus (TP) loads under the present and future scenarios by using the Soil and Water Assessment Tool (SWAT). To predicted the impacts of climate and land-use change on streamflow, sediment, and TP loads, there are 46 scenarios composed of historical climate, baseline period climate, eight climate models of Coupled Model Intercomparison Project phase 5 (CMIP5) of two representative emission pathways (RCP4.5 and RCP8.5), after downscaled and bias-corrected, two observed land-use maps (LULC1995, LULC2015) and the projected two future land use maps (LU2055 and LU2075) with the help of CA-Markov model to be fed into SWAT. The central tendency of streamflow, sediment, and TP loads under future scenarios is represented using the annual average. The intra-/ inter-annual variation of streamflow, sediment, and TP loads simulated by SWAT are also analyzed using the coefficient of variation. The results show that future land-use change has a negligible impact on annual streamflow, sediment, TP loads, and intra-annual and inter-annual variation. Climate change is likely to amplify the annual streamflow and sediment and reduce the annual TP loads, which is also expected to reduce its inter-/intra-annual variation of TP loads compared to the baseline period (2000-2019). The combined impact of land-use and climate change on streamflow, sediment, and TP loads are greater than the sum of individual impact for climate change and land-use change, especially for TP loads. Moreover, the synergistic impact caused by the interaction of climate and land use varies with variables and is more significant for TP loads. Thus, it is necessary to consider the combined climate and land-use change scenarios in future climate change studies due to the non-negligible synergistic impact, especially for TP loads. This research rare integrate the individual/ combined/ synergistic impact of land-use and climate change on streamflow, sediment, and TP loads and will help to understand the interaction between climate and land-use and take effective climate change mitigation policy and land-use management policy to mitigate the non-point source pollution in the future.